MERCHANDISING AS A SPECIAL MARKETING TECHNOLOGY - N. Vakurova; K. Golubeva; D. Kasparova (Вестник университета)
Based on the results of different researches, this article tells about merchandising as a special marketing technology, which stimulates an effective sales promotion. There is a brief description of types, ways and examples of the correct use of merchandising in foreign companies and problems of introduction this practice to a Russian retail segment.